From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Do not ignore the effects of phosphorus and potassium addition on microbial carbon use efficiency - Chenyang Zhang; Liyang Sun; Yichao Rui; Yue Li; Yiqi Luo; Minggang Xu; Andong Cai (Global Change Biology, 2023)

Species of fast bulk‐soil nutrient cycling have lower rhizosphere effects: A nutrient spectrum of rhizosphere effects - Lijuan Sun; Yuki Tsujii; Tianle Xu; Mengguang Han; Rui Li; Yunfeng Han; Dayong Gan; Biao Zhu (Ecology, 2023)
Tree roots not only acquire readily‐usable soil nutrients but also affect microbial decomposition and manipulate nutrient availability in their surrounding soils, that is, rhizosphere effects (REs). Thus, REs challenge the basic understanding of how plants adapt to the environment and co‐exist with other species. Yet, how REs vary among species in response to species‐specific bulk soil nutrient cycling is not well‐known. Here, we studied how plant‐controlled microbial decomposition activities in rhizosphere soils respond to those in their corresponding bulk soils and whether these relations depend on species‐specific nutrient cycling in the bulk soils. We targeted 55 woody species of different clades and mycorrhizal types in three contrasting biomes, namely a temperate forest, a subtropical forest, and a tropical forest. We found that microbial decomposition activities in rhizosphere soils responded linearly to those in their corresponding bulk soils at the species level. Thereafter, we found that REs (parameters in rhizosphere soils minus those in corresponding bulk soils) of microbial decomposition activities had negative linear correlations with microbial decomposition activities in corresponding bulk soils. A multiple factor analysis revealed that soil organic carbon, total nitrogen, and soil water content favored bulk soil decomposition activities in all three biomes, showing that the magnitude of REs varied along a fast‐slow nutrient cycling spectrum in bulk soils. The species of fast nutrient cycling in their bulk soils tended to have smaller or even negative REs. Therefore, woody plants commonly utilize both positive and negative REs as a nutrient‐acquisition strategy. Based on the trade‐offs between REs and other nutrient‐acquisition strategies, we proposed a push and pull conceptual model which can bring plant nutrient‐acquisition cost and plant carbon economics spectrum together in the future. This model will facilitate not only the carbon and nutrient cycling but also the mechanisms of species co‐existence in forest ecosystems.

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Decadal shift of the influence of Arctic Oscillation on dust weather frequency in spring over the Middle East during 1974–2019 - Yijie Sun; Rui Mao; Dao‐Yi Gong; Ying Li; Seong‐Joong Kim; Xiao‐Xiao Zhang; Xuezhen Zhang; Mehdi Hamidi (International Journal of Climatology, 2022)
Dust weather has an impact on human health and climate change in the Middle East. In this study, we examined the influence of the Arctic Oscillation (AO) on spring dust weather frequency over the Middle East at an interannual timescale during 1974–2019. The results show that there was an interdecadal shift of the influence of AO on dust weather frequency in the Middle East, with a correlation coefficient between the AO index and dust weather frequency changing from −0.52 during 1974–1994 period (P1) to 0.49 during 1995–2013 period (P2). During P1, negative correlations between AO index and dust weather frequency were found over the northern Arabian Peninsula, and during P2, positive ones were mostly over the central and southwestern Arabian Peninsula. In the lower and middle troposphere, negative geopotential height anomalies are associated with the negative phase of the AO over South Europe during P1, whereas negative geopotential height anomalies are associated with the positive phase of the AO over Northeast Africa during P2. The negative height anomalies resulted in the occurrence of more low‐pressure systems and, thus, dust weather in the Middle East. It is found that the interdecadal shift of the influence of the AO on dust weather was related to an AO‐related northward displacement of wave train propagation during P2. Specifically, during P1 period, the northern branch of AO‐related wave train dominated over the middle latitudes of the North Atlantic across South Europe to the Arabian Peninsula, which resulted in the negative height anomaly over South Europe in the lower and middle troposphere. However, during P2 period, the AO‐related wave train propagation moved northward, and then, the southern branch of the AO‐related wave train dominated over the low latitudes of the North Atlantic across northern Africa to the Arabian Peninsula, which played an important role in the formation of the negative height anomalies over Northeast Africa.

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

Metabolic potentials of members of the class Acidobacteriia in metal‐contaminated soils revealed by metagenomic analysis - Rui Xu; Xiaoxu Sun; Max M. Häggblom; Yiran Dong; Miaomiao Zhang; Zhaohui Yang; Enzong Xiao; Tangfu Xiao; Pin Gao; Baoqin Li; Weimin Sun (Environmental Microbiology, 2022)
Summary The relative abundance of Acidobacteriia correlated positively with the concentrations of arsenic (As), mercury (Hg), chromium (Cr), copper (Cu) and other metals, suggesting their adaptation of the metal‐rich environments. Metagenomic binning reconstructed 29 high‐quality metagenome‐assembled genomes (MAGs) associated with Acidobacteriia , providing an opportunity to study their metabolic potentials. These MAGs contained genes to transform As, Hg and Cr through oxidation, reduction, efflux and demethylation, suggesting the potential of Acidobacteriia to transform such metal(loid)s. Additionally, genes associated with alleviation of acidic and metal stress were also detected in these MAGs. Acidobacteriia may have the capabilities to resist or transform metal(loid)s in acidic metal‐contaminated sites. Moreover, these genes encoding metal transformation could be also identified in the Acidobacteriia ‐associated MAGs from five additional metal‐contaminated sites across Southwest China, as well as Acidobacteriia ‐associated reference genomes from the NCBI database, suggesting that the capability of metal transformation may be widespread among Acidobacteriia members. This discovery provides an understanding of metabolic potentials of the Acidobacteriia in acidic metal‐rich sites.

Gut microbiota in patients after surgical treatment for colorectal cancer - Ye Jin; Yang Liu; Lei Zhao; Fuya Zhao; Jing Feng; Shengda Li; Huinan Chen; Jiayu Sun; Biqiang Zhu; Rui Geng; Yunwei Wei (Environmental Microbiology, 2019)
Summary Colorectal cancer (CRC) is a common disease worldwide that is strongly associated with the gut microbiota. However, little is known regarding the gut microbiota after surgical treatment. 16S rRNA gene sequencing was used to evaluate differences in gut microbiota among colorectal adenoma patients, CRC patients, CRC postoperative patients and healthy controls by comparing gut microbiota diversity, overall composition and taxonomic signature abundance. The gut microbiota of CRC patients, adenoma patients and healthy controls developed in accordance with the adenoma‐carcinoma sequence, with impressive shifts in the gut microbiota before or during the development of CRC. The gut microbiota of postoperative patients and CRC patients differed significantly. Subdividing CRC postoperative patients according to the presence or absence of newly developed adenoma which based on the colonoscopy findings revealed that the gut microbiota of newly developed adenoma patients differed significantly from that of clean intestine patients and was more similar to the gut microbiota of carcinoma patients than to the gut microbiota of healthy controls. The alterations of the gut microbiota between the two groups of postoperative patients corresponded to CRC prognosis. More importantly, we used the different gut microbiota as biomarkers to distinguish postoperative patients with or without newly developed adenoma, achieving an AUC value of 0.72. These insights on the changes in the gut microbiota of CRC patients after surgical treatment may allow the use of the microbiota as non‐invasive biomarkers for the diagnosis of newly developed adenomas and to help prevent cancer recurrence in postoperative patients.

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.